Alternative proteins and EU food law. (December 2021) - Lähteenmäki-Uutela, Anu; Rahikainen, Moona; Lonkila, Annika; Yang, Baoru
Abstract: We ask how European food law impacts the transformative potential of alternative proteins, including single-cell proteins, plant-based novel proteins, cultured meat, macroalgae, and insects. The Novel Food Regulation may prove insurmountable for small companies, and it is demanding and time-consuming even for larger companies, dampening the transformative potential of all novel foods and traditional foods from third countries. Several microalgae and macroalgae are non-novel in the EU, which eases their way into the markets. The unclear novel food status of some potential green macroalgae species is a hindrance. All insects are novel, and none has EU-level authorization yet, although some Member States allow insect food. The GM Food Regulation is procedurally and scientifically demanding, and it forces GM labelling. The Regulation dampens the transformative potential of food GM technology. In addition to crops and fruit, GM Food Regulation applies to genetically modified or edited microbes, microalgae, cultured meat, and insects. The naming and labelling rules of plant-based products have caused controversy. From the business perspective, the health claims process is similarly challenging as the novel food process. EU food law must guarantee food safety and consumer rights while applying the principles of nondiscrimination and proportionality. Highlights: EU food law impacts the transformative potential of alternative proteins. Insects and cultured meat are novel foods; several microalgae and macroalgae are not. The GM Food Regulation applies to all genetically modified or edited foods. The names of vegan products have caused controversy. The principles of non-discrimination and proportionality are important for fairness.